University rankings as knowledge organization systems: An analysis of their classification nature - Guimarães, José Augusto Chaves [UNESP]; Holland, Helber [UNESP]; Campbell, D. Grant (My University, 2020)
Considering the knowledge organization system as a core issue in the knowledge organization field, this paper focuses on international university rankings as a new incarnation of KOS through an analysis of their classificatory nature. For this, three important international university rankings are analyzed: THE, Shanghai, and QS in terms of their notation, facets, citation order, editions, and updating. The results confirm their classificatory nature as essentially faceted systems whose structure is derived from specific contextual slants and whose dynamic updating process leads to a constant remodeling of the structure and the weight of the facets.
Rankings universitarios como sistemas de organización del conocimiento: Un análisis de su naturaleza clasificatoria
Keywords: Classificatory structures; Higher education rankings; Knowledge Organization Systems